PEMAHAMAN HUKUM DI MAN 2 SURAKARTA TENTANG PENYEBARAN BERITA BOHONG (HOAX) - Diana Lukita Sari (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2025)
The acceleration of information dissemination through social media and other digital platforms has made it increasingly difficult to control the flow of news. Limited ability to filter and select information presents a significant threat regarding the potential influence of fake news on society. Given that regulations alone are insufficient to curb the spread of hoaxes, enhancing public awareness is essential to mitigate the risk of incitement by misinformation. In response to this phenomenon, this community service initiative aims to provide understanding of the latest regulations related to hoaxes and preventive actions. This initiative was conducted at MAN 2 Surakarta, using varied lecture methods, video presentations, and interactive games such as identifying fake news. Through this program, we aim to increase students’ ability to critically assess information on social media, enabling students at MAN 2 Surakarta to better evaluate the validity of information and avoid the negative influence of hoaxes and potential incitement.